Pengaruh Kualitas Produk dan Citra Merek Terhadap Keputusan Pembelian Cat Nippon - Darmawansah Ibrahim (AhInstitute of Research and Community Service (LP2M) Institute of Social Sciences and Business Andi Sapada, 2025)
This study aims to examine the influence of product quality and brand image on purchasing decisions of Nippon Paint in Pinrang City, both partially and simultaneously. The background of this research stems from the increasingly intense competition in the paint industry, where consumers are faced with many product choices. To gain deeper insights into consumer behavior, this research adopts a descriptive quantitative approach using a survey method involving 56 respondents who are consumers of Nippon Paint. Data were collected through four instruments: observation sheets, questionnaires, interviews, and documentation. The independent variables in this study are product quality (including durability, color coverage, texture, and safety) and brand image (including recognition, reputation, and emotional appeal), while the dependent variable is the purchase decision. The data were analyzed using multiple linear regression with the assistance of SPSS version 27. The results show that product quality has a strong partial influence on purchasing decisions. Similarly, brand image also has a significant partial effect. Simultaneous testing indicates that both variables together make a meaningful contribution to purchasing decisions of Nippon Paint. The coefficient of determination (R²) reveals that more than 60% of the variation in purchasing decisions can be explained by product quality and brand image.